Prosthetic Rehabilitation of Patient with Mixed Connective Tissue Disease Using Glove Type Silicone Finger and Toe Prosthesis - Thilak Shetty1, Abhinav Sharma2, Shobha J Rodrigues3, Vidya K Shenoy4, Umesh Pai5, Sharon Saldanha5 (Indian Journal of Forensic Medicine & Toxicology, 2020)
The hand is a powerful tool and its loss causes a severe psychological and physical drawback. A considerable number of people each year suffer finger or partial finger amputations as a result of malignant disease, trauma, and congenital deformity.Prosthetic restoration is usually considered difficult for the whole or a part of the finger and it worsens if multiple fingers are involved. Additionally in patients with mixed connective tissue disorders with overlapping clinical features of scleroderma and arthritis any undue pressure from the artificial rings or vacuum fit of the prosthesis might cause further vasoconstriction that could worsen blood flow to extremities. This clinical report describes a simple and economical method for prosthetic rehabilitation of a patient with mixed connective tissue disease following digital loss using a custom made prosthesis with medical grade tissue adhesive as retentive aid.